How to handle stress for middle school success - Guerra, Silvi (Kid confident, 2023)
Offers stress-management advice and skills for middle school readers. Encourages middle schoolers on developing healthy habits for diet, sleep, and screen-times, on creating their own formula for feeling brave and courageous throughout their time in middle school, using the author's "Chill Hacks" to calm down when anxiety strikes, and how to develop a "can-do" attitude while controlling their response to worry and stress.